Biochemical effects of chromium, selenium and zinc elements on experimentally diabetic rats - Suzan Shawky Abuelkasem Muhamad; Hassan Abdelhalim Amer; Ismail Ibrahim Hegazy; Samy Ahmad Abdelaziz (Cairo : Suzan Shawky Abuelkasem Muhamad, 2018)
The present work was done to elucidate the possible protective and antioxidant effect of chromium chloride (CrCl) (500 mg/k.g.), sodium selenite (SeNa) (1.5 mg/k.g.) and Zinc sulphate (ZnSO4) (54 mg/k.g.) supplementation in streptozotocin induced diabetic rats. Oral administration of both Cr and Zn as well as intraperitoneal injection of Se at concentrations of 500, 54 and 1.5 mg/kg b.w. daily, respectively for 8 weeks showed a significant decrease in fasting blood glucose, total cholesterol (TC), triacylglycerols (TG), low density lipoprotein (LDL-C) and thiobarbituric acid reactive substances. The treatment also resulted in a significant increase in plasma C-peptide, blood reduced glutathione (GSH) and superoxide dismutase (SOD) as well as gene expression of heart glucose transporter 4 (GLUT4) of diabetic rats. Also, the results clearly suggest that the trace elements treated groups may effectively normalize the body weight as well as high density lipoprotein (HDL-C) in streptozotocin induced-diabetes. The trace elements exerted rapid protective effects against lipid peroxidation by scavenging of free radicals there by reducing the risk of diabetic complications. The effect was more pronounced by Cr supplementation as compared with Se and Zn supplementation
Thesis (Ph.D.) - Cairo University - Faculty of Veterinary Medicine - Department of Biochemistry and Chemistry of Nutrition
Issued also as CD
Keywords: Diabetic rats; Oxidative stress biomarkers; Trace elements